Pelatihan dan Penyuluhan Sertifikasi Desa Wisata di Desa Cibuntu - Habibi, Fachrul Husain; Arafah, Willy; Mustika, Amalia; Ratnaningtyas, Heny (Jurnal Pemberdayaan Pariwisata; Vol 3 No 2 (2021): Jurnal Pemberdayaan PariwisataDO - 10.30647/jpp.v3i2.1599, 2021)
Tourism village certification is part of the framework of the sustainable tourism development program or Indonesian sustainable tourism. The purpose of this research is that village managers and the community will understand the importance of tourism village certification which guarantees to tourists the quality of tourist village destinations. The method of activity used in this activity is counseling and training. This service activity was carried out at the Cibuntu Village Hall starting at 08.00 to 13.00, which was attended by 20 participants. It is hoped that this service activity will make the managers and the tourism village community better understand the concept of quality assurance for good tourism village management, including the process of establishing and fulfilling management quality standards in a consistent and sustainable manner, so that consumers, producers, and stakeholders get satisfaction.